Judicial accountablity or illusion? - Bhushan, Prashant (2006)
The national judicial council, which will be constituted with the enactment of the proposed judicial council bill, will only create an illusion of acountability of the higher judiciary. - Reproduced.
Keywords: Judiciary - India; Judiciary